2020
DOI: 10.1371/journal.pone.0235779
|View full text |Cite
|
Sign up to set email alerts
|

Prostate MRI added to CAPRA, MSKCC and Partin cancer nomograms significantly enhances the prediction of adverse findings and biochemical recurrence after radical prostatectomy

Abstract: Background To determine the added value of preoperative prostate multiparametric MRI (mpMRI) supplementary to clinical variables and their role in predicting post prostatectomy adverse findings and biochemically recurrent cancer (BCR). Methods All consecutive patients treated at HUS Helsinki University Hospital with robot assisted radical prostatectomy (RALP) between 2014 and 2015 were included in the analysis. The mpMRI data, clinical variables, histopathological characteristics, and follow-up information wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 33 publications
0
9
0
1
Order By: Relevance
“…A number of groups are now also exploring using MRI in screening trials although at this juncture it is unclear if MRI will pass the Wilson and Jungner criteria to reduce mortality or perhaps only in helping reduce the harms of screening [27,28]. At a more immediate level MRI is being proposed as a useful adjunct to risk stratification in decision making albeit with surrogate markers of outcome such as adverse pathology, biochemical relapse free survival or progression rates on Active Surveillance [29][30][31][32]. In contrast there is uncertainty on whether MRI will actually improve long-term survival outcomes [10,13,33].Modelling studies so far have found little evidence for this and MRI may in fact contribute to over-diagnosis and over-treatment [10].…”
Section: Discussionmentioning
confidence: 99%
“…A number of groups are now also exploring using MRI in screening trials although at this juncture it is unclear if MRI will pass the Wilson and Jungner criteria to reduce mortality or perhaps only in helping reduce the harms of screening [27,28]. At a more immediate level MRI is being proposed as a useful adjunct to risk stratification in decision making albeit with surrogate markers of outcome such as adverse pathology, biochemical relapse free survival or progression rates on Active Surveillance [29][30][31][32]. In contrast there is uncertainty on whether MRI will actually improve long-term survival outcomes [10,13,33].Modelling studies so far have found little evidence for this and MRI may in fact contribute to over-diagnosis and over-treatment [10].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have proven the added value of mp-MRI and MRI-targeted Bx in the prediction of ECE and SVI before RP. 2 , 22 , 26 Sandeman et al . 22 reported that adding mp-MRI parameters to the Memorial Sloan Kettering Cancer Center (MSKCC) nomogram and Partin tables can further improve the prediction efficiency of these models for any adverse finding at RP and increase AUCs from 0.71 to 0.78 and from 0.62 to 0.73, respectively.…”
Section: Discussionmentioning
confidence: 99%
“… 21 The sensitivity, specificity, positive predictive value (PPV), negative predictive value (NPV), and accuracy were then derived according to the threshold. Based on the parameters used in previous studies, 2 , 22 univariate analysis was performed first to select associated factors with P < 0.05. Then, binary logistic regression (LR) analysis was performed, and independent variables were selected using the forward LR method for the regression model.…”
Section: Methodsmentioning
confidence: 99%
“…The study by Meijer et al [1] adds to a growing body of evidence that local staging of prostate cancer with MRI is clinically important, particularly when seminal vesicle invasion is found [2][3][4]. The current TNM classification is clearly at odds with this evidence as it states that MRI findings should not be used for local (T) staging [5].…”
mentioning
confidence: 99%